Recurrent Thyrotoxicosis due to Both Graves' Disease and Hashimoto's Thyroiditis in the Same Three Patients - Schaffer, Ashley (Case Rep Endocrinol, 2016)
Hashimoto's thyroiditis (HT) and Graves' disease (GD) are the 2 most common autoimmune disease processes affecting the thyroid gland. The relationship between the two is complex and not clearly understood. It has been theorized that HT and GD are 2 separate disease processes due to unique genetic differences demonstrated by genome studies. On the other hand, based on occurrence of both HT and GD in monozygotic twins and within the same family, they have been regarded to represent 2 ends of the same spectrum. This case report describes 3 patients who presented with thyrotoxicosis due to both GD and HT. The initial presentation was thyrotoxicosis due to GD treated with antithyroid medication followed by temporary resolution. They all subsequently experienced recurrence of thyrotoxicosis in the form of Hashitoxicosis due to HT, and then eventually all developed thyrotoxicosis due to GD, requiring radioablation therapy.